2016
DOI: 10.1080/02640414.2015.1134805
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, physical activity and neuromuscular performance in children

Abstract: Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.tandfonline.com: http://dx.doi.org/10. 1080/02640414.2015.1134805 This is the final text version of the article, and it may contain minor differences from the journal's pdf version. The authors declare no conflicts of interest. ABSTRACT 3We investigated the associations of body fat percentage, objectively assessed moderate-to-vigorous physical activity (MVPA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
2
12
0
3
Order By: Relevance
“…12 Recent research indicates that higher body fat and lower PA level were associated with poorer neuromuscular performance, assessed with the same tasks that we had in our study; shuttle-run and sit-ups. 35 An earlier study highlighted the complex interrelationships among PA, body fat, and motor performance and suggested similar conclusions as we do, in terms of the association being strongest between motor performance and body fat. 36 However, in both of these studies described above, the body composition measurements used were diverse.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…12 Recent research indicates that higher body fat and lower PA level were associated with poorer neuromuscular performance, assessed with the same tasks that we had in our study; shuttle-run and sit-ups. 35 An earlier study highlighted the complex interrelationships among PA, body fat, and motor performance and suggested similar conclusions as we do, in terms of the association being strongest between motor performance and body fat. 36 However, in both of these studies described above, the body composition measurements used were diverse.…”
Section: Discussionsupporting
confidence: 88%
“…Earlier research has shown that overweight children may have difficulties in locomotor activities compared to children with healthy weight . Recent research indicates that higher body fat and lower PA level were associated with poorer neuromuscular performance, assessed with the same tasks that we had in our study; shuttle‐run and sit‐ups . An earlier study highlighted the complex interrelationships among PA, body fat, and motor performance and suggested similar conclusions as we do, in terms of the association being strongest between motor performance and body fat .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, a previous study revealed that disability significantly affected the muscle mass [ 60 ]. Furthermore, according to previous studies, children who are more physically active may have lower percent body fat values and higher muscle mass values [ 61 , 62 ]. The findings of a Chinese study group [ 63 ] and those of Babirekere-Iriso et al [ 64 ] indicated that physical activity may have a vital role in the development of skeletal muscle mass in children.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels physical activity has been linked to better brain functions and structures, cognitive functions, and academic achievement in children and adolescents in some, but not all, cross-sectional studies [33]. While some studies have found an association between objectively measured physical activity, cognition, and academic achievement [43][44][45], others have shown weak, if any, associations of objectively measured physical activity with cognition and academic achievement in children [46][47][48][49] Exercise interventions also have provided some evidence that increasing after-school or classroom physical activity improve cognitive functions and academic achievement in children [50][51][52]. Increasing physical exercise levels has been related to structural changes in the brain and subsequently with better cognition and academic achievement in comparison to sedentary individuals [33,53].…”
Section: Physical Activity and The Brainmentioning
confidence: 99%